2021
DOI: 10.5423/ppj.nt.03.2021.0053
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic and Plant Growth-Promoting Effects of Bacillus velezensis BS1 Isolated from Rhizosphere Soil in a Pepper Field

Abstract: Pepper ( Capsicum annuum L.) is an important agricultural crop worldwide. Recently, Colletotrichum scovillei , a member of the C. acutatum species complex, was reported to be the dominant pathogen causing pepper anthracnose disease in South Korea. In the present study, we isolated bacterial strains from rhizosphere soil in a pepper field in Gangwon Province, Korea, and assessed their antifungal ability against C. scovillei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In addition, according to Shahid et al (2021), the antifungal activity of Bacillus can also fight other agricultural pathogens, such as Fusarium oxysporum, Fusarium moniliforme, and Colletotrichum falcatum (Shahid et al 2021). Other results in the study of Shin et al (2021) also showed that B. velezensis BS1 could promote the growth of chili seedlings. In the phylogenetic tree, Bacillus thuringiensis is an outgroup.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, according to Shahid et al (2021), the antifungal activity of Bacillus can also fight other agricultural pathogens, such as Fusarium oxysporum, Fusarium moniliforme, and Colletotrichum falcatum (Shahid et al 2021). Other results in the study of Shin et al (2021) also showed that B. velezensis BS1 could promote the growth of chili seedlings. In the phylogenetic tree, Bacillus thuringiensis is an outgroup.…”
Section: Discussionmentioning
confidence: 97%
“…ES4.3 with B. velezensis BS1 and B. velezensis FZB42. This strain was found from pepper fields in Gangwon Province, Korea. Based on the research of Shin et al (2021), they said that B. velezensis BS1 was consistently able to produce cellulase, proteases, and siderophores; and inhibited the growth, appressorium formation, and disease development of Colletotrichum scovillei Damm, P.F.Cannon & Crous, a pepper anthracnose pathogen. B. velezensis BS1 showed a high inhibitory effect on the mycelium growth of Botrytis cinerea isolated from strawberries, Rhizoctonia solani and Sclerotinia sclerotiorum (Lib.)…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth-promoting bacteria (PGPB) can enhance plant yield and control phytopathogens, constituting the most widely studied and increasingly used tool in modern agriculture ( Emmanuel and Babalola, 2020 ). Bacillus is one of the more widely studied PGPB, which is partly due to its production of ACC deaminase, indole-3-acetic acid (IAA), organic acids, siderophores, and phosphate solubilization ( Khan et al, 2020 ; Shin et al, 2021 ). Our study showed that the application of B. siamensis YC-9 significantly increased the dry weight, fresh weight, plant height, and root length of cucumbers in pot experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Several strains of B. velezensis isolated from various hosts have demonstrated broad-spectrum antimicrobial and plant growth-promoting properties [ 31 , 32 ]. B. velezensis has been used as an antagonist of plant pathogens and a plant growth promoter in sustainable agriculture [ 4 ]; for example, the B. velezensis strain BS1, isolated from rhizospheric soil in a pepper field, has shown immense potential as a new BCA for controlling pepper anthracnose disease [ 33 ]. In this study, the isolated strain RDA1 showed strong antagonistic effects against soil-borne fungal phytopathogens and inhibited the mycelial growth of R. necatrix (KACC 40445, KACC 40446, KACC 40447, and KACC 40168).…”
Section: Discussionmentioning
confidence: 99%